Parenting Styles and Affective and Emotional Development on Children - Frías Armenta , Martha (Consorcio de Universidades Mexicanas A.C., 2013)
Family is the place where children enjoy their first interactions with the world. Parents provide children emotional, social as well as learning support. Mothers in particular, invest substantial time and energy on their children so they can survive and grow to be successful adults. In theory, mothers and fathers seek to invest in the upbringing of their children in order for them to achieve a process of adaptation and survival in the environment in which they live; therefore, they look for the best tools to achieve this goal. In this sense, the aim of this study is to investigate the perception of mothers and fathers about their parenting styles. The sample was 201 mothers and fathers of Hermosillo, Sonora, Mexico, a northwestern city of Mexico. Students of psychology interviewed the parents in their houses. Descriptive statistics, t student and chi square were used for data analysis. Results indicate that parents identify themselves as good, responsible, loving and they do not report the use of physical punishment. We can conclude that parents have a positive perception of their parenting and educational styles.